Controlled coupling and characterization of oyster (Crassostrea gigas) ferritin with gold nanostars - Han Li; Xiaoyu Xia; Shuzhen Cheng; Jiachen Zang; Zhenyu Wang; Xianbing Xu; Ming Du (Food Science and Human Wellness)
Ferritin has good thermal stability, resistance to certain acids and bases, and targeting, and has broad application prospects in the synthesis of gold nanostars (AuNS). In this study, we screened monodisperse AuNS with uniform particle size and morphology through a one-step synthesis method and coupled the synthesized AuNS with oyster ferritin (GF1). The results showed that the surface plasmon resonance (SPR) peaks of the coupled GF1@AuNS changed significantly, and the changes in infrared spectra and potential confirmed the success of the synthesis, while the microscopic morphology showed an increase in particle size and surface peak coverage. Furthermore, GF1@AuNS does not induce cell death in the 100 μmol/L range, is highly stable in physiological environments, and exhibits good X-ray attenuation in micro-computed tomography. Due to the unique functional activity of ferritin and AuNS, GF1@AuNS has potential applications in food detection and drug development in the future.